Nitrogen and carbon stable isotope data for Queen scallop Aequipecten opercularis (Linnaeus, 1758) (AphiaID: 140687) muscle tissue - Jennings, Simon (Dryad Digital Repository, 2016)
The file comprises measurements of carbon and nitrogen stable isotope composition in the adductor muscle tissue of 535 individual Queen scallop Aequipecten opercularis sampled from northeast Atlantic shelf seas in 2001 and 2010. Data collection and existing analyses are described in the following publications: (1) Barnes, C., Jennings, S. & Barry, J.T. (2009) Environmental correlates of large-scale spatial variation in the δ13C of marine animals. Estuarine, Coastal and Shelf Science, 81, 368-374; (2) Jennings, S. & Warr, K.J. (2003) Environmental correlates of large-scale spatial variation in the δ15N of marine animals. Marine Biology, 142, 1131-1140; (3) Jennings, S. & Van der Molen, J. (2015) Trophic levels of marine consumers from nitrogen stable isotope analysis: estimation and uncertainty. ICES Journal of Marine Science, 72, 2289-2300. Additional descriptions of the data structure and data collection process are provided in the accompanying "readme" file.